Tra il reato e la persona - Liberata di Lorenzo; Gerardo Pastore (Culture e Studi del Sociale)
This paper focuses on the strategic nature of prison treatment activities proposed to men convicted of violent crimes against women. In a constant movement between theoretical dimensions and transformative practices, we will place at the centre of the analytical process questions about the social and cultural elements that legitimise and favour the reproduction of male acts of violence. The intention is to go beyond the dominant culture of vengeance, which, especially in the case of this type of crime, invokes extreme solutions that are well summed up by the common proposal to lock the perpetrator up in prison and "throw away the key". A solution that, as is obvious, is in stark contrast to the constitutional dictate, which provides for sentences aimed at the re-education of the convicted person. But what actually happens to perpetrators of violence against women in prison? What are the difficulties of treatment? What is the purpose of the proposed courses?What are the results?Starting from these questions, we will provide cognitive elements resulting from work and research experiences in a Tuscan prison.We will focus on the person, the adherence to the internal treatment paths, the practices of resistance, the difficulties, the processes of denial and/or awareness.